Shaping multisine excitation for closed-loop identification of a flexible transmission. Issue 7 (2021) - Boukhebouz, Bassem; Mercère, Guillaume; Grossard, Mathieu; Laroche, Édouard
Abstract: In this paper, a heuristic solution is suggested to tune a bounded amplitude multisine control signal in a closed-loop setup. The solution consists in the combination of two algorithms: (i) a first one that minimizes the Crest Factor of the control signal and (ii) a second one to shape the spectrum of the control signal so that it converges to a desired signal via the tuning of the reference spectrum. Considering a flexible motor-to-joint mechanical transmission, an illustrative example based on simulated data shows that the suggested solution allows to avoid nonlinear distortions created by the control signal bounds, thus improving the estimation of the frequency response function.